Teologi Asy’ari dalam Kitab Tafsir (Analisa Metode Ta’wil Tafṣīlī dalam Memahami Ayat Istiwā’) - Abdulloh Dardum (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2017)
Among the mutasyābihāt verses, there are verses which speak about Allah SWT substances, such as verses about hands, eyes, face, istawa', and so on. This article specifically tries to expose and review the ta'wīl tafṣīli method used by the mufasir in understanding the Istiwa' verses. Some of the mufasir mentioned in this article are Ibnu Jarir al-Thabari (w. 310 H), Abu Bakr Ahmad al-Razi al-Jassas al-Hanafi (w. 370 H), Abu al-Laith Nasr bin Muhammad bin Ahmad bin Ibrahim al-Samarqandi (w. 375 H), Abu Hasan Ali bin Muhammad al-Mawardi (w.450 H), Abu Hasan Ali bin Ahmad al-Wahidi al-Naisaburi (w. 468 H), Abu Muhammad Abdul Haq bin' Athiyyah al-Andalusiy (w. 541 H), Fakhruddin al-Razi al-Shafi'i (w. 606 H), Abu Abdillah Muhammad bin Ahmad al-Ansari al-Qurthubi (w. 671 H), Nasiruddin Abdul Khair Abdullah bin Umar ibn Muhammad al-Baidawi al-Shafi'i (w. 685 H), Abu al-Barkat Abdullah bin Ahmad al-Nasafi (w. 710 H), Abu Hayyan al-Andalusiy (w. 754 H), and Abdurrahman bin Muhammad bin Makhluf Abu Zaid al-Tha'alabi (w. 875 H). Using the ta'wīl method, it was found that the majority of the mufasir did not understand istawa' literally. They do not believe that the meaning of istawa' is that Allah sits or stays at the 'Arsy. They turn the meaning of istawa' from its literal meaning to another meaning which corresponds to His greatness traits. They interpret istawa' with istawla or qahara which means to dominate or to conquer. The choice of the ta'wil method is a logical consequence to reinforce Asy'ari's ideology which believes that Allah exists without any place.